PWE-332 A pilot randomised controlled trial using objective video assessment to investigate the impact of the interval between long-course chemoradiotherapy and resection of advanced rectal cancer upon technical performance of surgery. (22nd June 2015) - Foster, J; Falk, S; Ewings, P; Williams-Yesson, B; Hanna, G; Francis, N
Abstract : Introduction: The optimal time to perform rectal cancer resection following long-course chemoradiotherapy (CRT) remains unclear. Many surgeons now elect to operate after a longer interval than the 6–8 weeks that was generally considered standard practice over the last decade. A longer interval may allow more precise surgery by allowing the radiation-induced inflammation to settle. The aim of this pilot multi-centre randomised controlled trial (RCT) was to evaluate the impact of the interval between CRT and surgery upon the technical complexity of the surgery. It was proposed that if a significant difference in complexity was found in this pilot study then progression to a large multi-centre RCT investigating the impact of the CRT-surgery interval upon rate of R0 resection would be indicated. Method: Patients with rectal cancer requiring long-course CRT were recruited from seven centres between June 2012 and May 2014. Consenting patients were randomised to have surgery after an interval of either 6 weeks or 12 weeks following completion of long-course CRT. Expert interviews were used to generate a structured checklist describing the technical steps of the operation and a list of potential errors of the technical performance that may occur. Operations were video-recorded and unedited videos were analysed by a blinded research fellow against the structured checklist using an objective methodology to identify technical errors enacted. Additionally, the operating surgeons completed visual analogue scales to document their perception of the complexity of the procedure. Data were also collected on radiological downstaging, clinical outcomes to 30-days post-operation, quality of life, and pathological specimen completeness. Results: Thirty one patients were enrolled into the study: 15 were randomised to a 6-week interval and 16 patients to 12-weeks. Four patients in the 6-week arm and two in the 12-week arm did not undergo surgery. Additionally, one patient in each arm was found to have unresectable disease at the time of surgery. Amongst the 23 patients who underwent resection there was no difference in frequency of errors identified per case between trial arms (p = 0.401), nor a difference in surgeon-reported complexity. No mortalities occurred. Other outcomes were similar between groups. Conclusion: Objective video assessment of technical performance of surgery has been successfully used within the context of a pilot multi-centre RCT. The timing to surgery has no significant impact on error frequency between a 6-week or 12-week CRT-surgery interval. Disclosure of interest: None Declared.